Exchange rate modeling under unconventional monetary policy on a European panel sample - Gábor Dávid Kiss; Mercédesz Mészáros (European Financial and Accounting Journal, 2019)
Following the latest subprime crisis, central banks introduced several unconventional instruments which had spillover effects on foreign exchange rates. The aim of our paper is to explore whether the use of zero lower bound (ZLB) and unconventional instruments has an impact on the changes in foreign exchange rates. By running dynamic panel regressions, we analysed this issue on a sample of 7 European central banks. Based on our results, unconventional monetary policy had a significant impact on the exchange rate fluctuations in the short term, even with the use of instruments where there was no targeted exchange rate regulation.
Keywords: E52; E58; E43; C33; 650; Interest Rate Parity; Unconventional Monetary Policy; Panel Regression